2019
DOI: 10.1002/advs.201900341
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Dynamic Peroxynitrite Fluxes in Epileptic Brains with a Near‐Infrared Fluorescent Probe

Abstract: Epilepsy is a chronic neurodegenerative disease, and accumulating evidence suggests its pathological progression is closely associated with peroxynitrite (ONOO − ). However, understanding the function remains challenging due to a lack of in vivo imaging probes for ONOO − determination in epileptic brains. Here, the first near‐infrared imaging probe (named ONP) is presented for tracking endogenous ONOO − in brains of kainate‐induced epileptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 65 publications
0
46
0
2
Order By: Relevance
“…In 2019, Qian et al reported a NIR fluorescent probe ONP and demonstrated that it could be used to trace endogenous ONOO À signals in kainate (KA)-induced epileptic seizures while providing a means for screening antiepileptic inhibitors. 16 ONP was developed using methylene blue (MB) as the reporter agent with a boronic ester serving as a selective reactive moiety for ONOO À (Fig. 9).…”
Section: Small Molecule-based Fluorescent Probes For Epilepsymentioning
confidence: 99%
“…In 2019, Qian et al reported a NIR fluorescent probe ONP and demonstrated that it could be used to trace endogenous ONOO À signals in kainate (KA)-induced epileptic seizures while providing a means for screening antiepileptic inhibitors. 16 ONP was developed using methylene blue (MB) as the reporter agent with a boronic ester serving as a selective reactive moiety for ONOO À (Fig. 9).…”
Section: Small Molecule-based Fluorescent Probes For Epilepsymentioning
confidence: 99%
“…The typical procedure to introduce such a residue exploits the 4-hydroxymethylphenylboronic acid pinacol ester in which the hydroxyl group is converted, often in situ , into an acid chloride in a reaction with triphosgene (Srikun et al, 2008 ; Chung et al, 2011 ; Zhu D. et al, 2013 ) in the presence of a base in various solvents, which reacts further with the target amino group. There are some examples in which this approach is also used to mask the nitrogen atom on biotin (Chung et al, 2018 ; Wu Y. P. et al, 2018 ) or methylene blue (Hu et al, 2019 ) or in aliphatic systems (Lippert et al, 2010 ; Zhu D. et al, 2013 ; Yik-Sham Chung et al, 2018 ).…”
Section: Synthetic Approaches To Boronate-based Molecular Probesmentioning
confidence: 99%
“…Real-time, in-vivo monitoring of biothiol changes would be bene cial for early diagnosis, prevention and therapeutic development for personalized AD management. Recently, multi-signal uorescent probes have been widely applied to observe and detect biothiols in-situ, due to their high selectivity, sensitivity, and operational simplicity [15,16]. It is of great value to utilized multi-signal uorescent probes to observe and quantify biothiols in AD patients and nerve cells, because this may help to con rm the associations between AD and Hcy levels by direct measurement in real-time.…”
Section: Introductionmentioning
confidence: 99%